Phenotypic Responses of Some Functional Traits in Four Native Perennial Grass Species Grown on Fly Ash Dump and Native Soil - Kumar, Vijay; Babu, Cherukuri Raghvendra (Frontiers in Plant Science, 2022)
Functional response traits of four perennial grass species (Imperata cylindrica, Cenchrus ciliaris, Sporobolus diander and Cynodon dactylon) growing on the fly ash dump and referal site having native soil were evaluated with the objective of selecting species suitable for rapid development of vegetation cover on the fly ash dumps. All the four species showed spectacular plastic responses in functional traits of plants grown on the fly ash dump and are induced by habitat and hence are adaptive. The traits associated with root system such as root length, spread, volume of the substratum occupied by root system and root biomass showed greater plasticity than the traits of the shoot system such as shoot biomass, mean number of tillers per clump and mean height of tillers. This suggests greater allocation of resources to root than to shoot by the species for space exploitative growth that enable them to acquire nutrients from nutritionally poor and unfavorable substratum like fly ash dump. Such a strategy enables species to establish and regenerate on barren areas including fly ash dumps. The higher root length, spread, biomass and root:shoot ratio in plants of all the species grown on fly ash as compared to plants grown on the native soil substantiates that plasticity in functional traits enabled the species to adapt to stressed habitats. The plastic responses observed are specific to the trait, specific to the species and specific to the environment. This is evident by the quantitative differences in the responses between traits within a species, between species and between habitats. The phenotypic plasticity induced by the fly ash altered the relationships between functional traits of the plants. This is evident by the marked differences in the r-values for different character associations between plants grown on fly ash dump and native soil. The results suggest that all the four grass species evaluated can be used for rapid development of vegetation cover on the fly ash dumps to mitigate environmental contamination.